2014
DOI: 10.1088/0964-1726/23/3/035014
|View full text |Cite
|
Sign up to set email alerts
|

Control of conducting polymer actuators without physical feedback: simulated feedback control approach with particle swarm optimization

Abstract: Conducting polymer actuators have shown significant potential in articulating micro instruments, manipulation devices, and robotics. However, implementing a feedback control strategy to enhance their positioning ability and accuracy in any application requires a feedback sensor, which is extremely large in size compared to the size of the actuators. Therefore, this paper proposes a new sensorless control scheme without the use of a position feedback sensor. With the help of the system identification technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…We have found that the four smooth inputs consume less electrical power than sharp inputs such as a step input with discontinuous higher order derivatives. We also obtained an improved transient response performance from the smooth inputs, especially under the simulated feedback control strategy, which we have proposed previously [13]. The idea of using a smooth input command, which results in lower power consumption and better control performance, can be extended to other smart actuators.…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…We have found that the four smooth inputs consume less electrical power than sharp inputs such as a step input with discontinuous higher order derivatives. We also obtained an improved transient response performance from the smooth inputs, especially under the simulated feedback control strategy, which we have proposed previously [13]. The idea of using a smooth input command, which results in lower power consumption and better control performance, can be extended to other smart actuators.…”
Section: Introductionmentioning
confidence: 73%
“…The structure of a PPy actuator [13] As shown in Figure 2, when a potential difference is applied to the actuator via platinum contacts, the PPy on positive electrode is oxidized and on the other hand, the negatively charged PPy layer is reduced. The TFSI -anions in the electrolyte will move into the positively charged PPy layer and cause a volume expansion.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations